Reliability and criterion validity of an observation protocol for working technique assessments in cash register work - Palm, P.; Josephson, M.; Mathiassen, Svend; Kjellberg, K. (Taylor & Francis, 2016)
© 2015 Informa UK Limited, trading as Taylor & Francis Group. We evaluated the intra- and inter-observer reliability and criterion validity of an observation protocol, developed in an iterative process involving practicing ergonomists, for assessment of working technique during cash register work for the purpose of preventing upper extremity symptoms. Two ergonomists independently assessed 17 15-min videos of cash register work on two occasions each, as a basis for examining reliability. Criterion validity was assessed by comparing these assessments with meticulous video-based analyses by researchers. Intra-observer reliability was acceptable (i.e. proportional agreement  > 0.7 and kappa  > 0.4) for 10/10 questions. Inter-observer reliability was acceptable for only 3/10 questions. An acceptable inter-observer reliability combined with an acceptable criterion validity was obtained only for one working technique aspect, ‘Quality of movements’. Thus, major elements of the cashiers’ working technique could not be assessed with an acceptable accuracy from short periods of observations by one observer, such as often desired by practitioners. Practitioner Summary: We examined an observation protocol for assessing working technique in cash register work. It was feasible in use, but inter-observer reliability and criterion validity were generally not acceptable when working technique aspects were assessed from short periods of work. We recommend the protocol to be used for educational purposes only.